Patriots in "Kala Pani?": Writing subaltern resistance into the nationalist memory - Zehmisch, Philipp (Cultural histories of India, 2020)
The widely known allegory of “Kala Pani” gained particular traction in the first decades of the twentieth century when narratives and reports about the